PP.18.09: TARGET ORGAN DAMAGE IN CARDIOVASCULAR LOW RISK PATIENTS WITH HIGH CENTRAL AORTIC PRESSURE. (June 2015) - Piskorz, D.; Tommasi, A.
Abstract : Objective: The aim of the present study is to determine if an elevated systolic aortic pressure is a marker of more frequent target organ damage (TOD) in hypertensive low cardiovascular risk (CVR) patients. Design and method: Hypertensive non treated consecutive patients (p) assisted at first visit in a specialized center with a CVR according to WHO Americas B area score less than 10 % were included. Left ventricular mass index (LVMI) and tissue Doppler diastolic and systolic function was measured as Lang RM et al JASE 2005 and Nagueh SF et al JASE 2009. Cardiac TOD was considered according to 2013 ESH/ESC Guidelines J Hypertension 2013. Glomerular filtration rate was calculated by MDRD formula, a value < 60 ml/min/1, 73m2 was considered TOD. Systolic aortic pressured (CAoP) was measured by radial tonometry and classified as McEniery CM et al Hypertension 2008. Continue variables are reported as means with standard deviation and discrete variables as absolute values and percentages. Statistical analysis was performed with Students t test, significant differences were considered with a p value < 0.05. Results: 159 p were included; 108 p (67.9%) had elevated CAoP while 51 p (32.1%) had normal CAoP. Sample mean age was 54.3+-12.9 years; 84 p (52.8 %) were males. Type 2 Diabetes had 4 p (2.5%), dyslipidemia 47 p (29.6%), and smokers were 18 p (11.3%). Mean blood pressure was 130.4+-11.7 mm Hg/77.1+-10.6 mm Hg in p with normal CAoP and 127.7+-10.4 mm Hg/75.1+-8.6 mm Hg in p with CAoP elevated (p = NS). Mean CAoP in p with normal values was 117.6+-11.4 mm Hg and 116.3+-9.9 in p with elevated values (p = NS). The table shows TOD data: Figure. No caption available. Conclusions: At the same level of CVR according to WHO Americas B score patients with elevated CAoP had higher left ventricular end diastolic pressure, lower longitudinal left ventricular systolic function and the renal function was more deteriorated.